The uncollected stories of Allan Gurganus - Gurganus, Allan, 1947- (Liveright Publishing Corporation, a division of W. W. Norton & Company, 2021)
"From one of "the best writers of our time" (Ann Patchett) comes a sparkling volume of previously uncollected short stories. For over three decades, Allan Gurganus has been heralded by readers and critics alike as "the most technically gifted and morally responsive writer of his generation" (John Cheever). Now, the beloved North Carolina author of such classics as Oldest Living Confederate Widow Tells All and White People has collected ten of his most powerful short stories-all of which have never appeared in a book and some of which have never before been published-into a volume that affirms his place as a quintessential Southern writer. In his characteristic style, Gurganus limns remarkable vignettes with unforgettable characters, such as Esther, the grammar school librarian who develops a relationship with a snake farmer in My Heart is a Snake Farmer, and the narrator of A Fool for Christmas, Vernon Ricketts, who is manager of Fin, Fur and Fun: "Third-busiest pet store in eastern North Carolina, so they tell me." Replete with descriptive prose that would remind one of none other than Melville, Uncollected Stories" celebrates one of the South's most iconic living authors and promises to create a new generation of Allan Gurganus readers for years to come"--Provided by publisher.